Impact of closed loop stimulation on prognostic cardiopulmonary variables in patients with chronic heart failure and severe chronotropic incompetence: a pilot, randomized, crossover study. Issue 11 (13th May 2021) - Proff, Joachim; Merkely, Béla; Papp, Roland; Lenz, Corinna; Nordbeck, Peter; Butter, Christian; Meyerhoefer, Juergen; Doering, Michael; MacCarter, Dean J; Ingel, Katharina; Thouet, Thomas; Landmesser, Ulf; et al.
Abstract: Aims: Clinical effects of rate-adaptive pacing in heart failure patients with chronotropic incompetence (CI) undergoing cardiac resynchronization therapy (CRT) remain unclear. Closed loop stimulation (CLS) is a new rate-adaptive sensor in CRT devices. We evaluated the effectiveness of CLS in CRT patients with severe CI, focusing primarily on key prognostic variables assessed by cardiopulmonary exercise (CPX) testing. Methods and results: In the randomized, crossover, multicentre BIO|CREATE study, 20 CRT patients with severe CI and NYHA Class II/III (60%/40%) were randomized 1:1 to the sequence DDD-40 mode to DDD-CLS mode, or the sequence DDD-CLS mode to DDD-40 mode (1 month in each mode). Patients underwent symptom-limited treadmill-based CPX test in each mode. An improvement (decrease) of the ventilatory efficiency (VE) slope of ≥5% during CLS was regarded as positive response to CLS. Seventeen patients with full data sets had a mean intra-individual VE slope change of −1.8 ± 3.0 (−4.1%) with CLS ( P  =   0.23). Eight patients (47%) were CLS responders, with a −6.1 ± 2.7 (−16.4%) slope change ( P  =   0.029). Compared to non-responders, CLS responders had a higher left ventricular (LV) ejection fraction (46 ± 3 vs. 36 ± 9%; P  =   0.0070), smaller end-diastolic LV volume (121 ± 34 vs. 181 ± 41 mL; P  =   0.0085), smaller end-systolic LV volume (65 ± 23 vs. 114 ± 39 mL; P  =   0.0076), and were predominantly in NYHA Class II ( P  =   0.0498). Conclusion: The data of the present pilot study are compatible with the notion that CLS activation may improve VE slope in CRT patients with severe CI and less advanced heart failure. Further research is needed to determine the long-term clinical outcomes of CLS.